Local Language Vitality in Indonesian Tourism Destinations: Tourism-Driven Language Shift and Preservation - Muin, Abdul; Arma, Arma; Afif, Muhamad; Pratiwi, Herlina; Hilmiyati, Fitri; Ansori, Aan (Khazanah Sosial, 2026)
This study examines the development and vitality of local languages in four major tourism destinations in Indonesia—Bali, Yogyakarta, West Java, and Banten by exploring how tourism-driven dynamics contribute to language shift and reshape cultural identity. The research is motivated by the growing dominance of Indonesian and English within tourism spaces, which progressively replaces the communicative functions of local languages and weakens intergenerational transmission, particularly among younger speakers. The primary aims of this study are to map the vitality levels of local languages, identify the key drivers of language shift, and analyze community-based preservation strategies that continue to operate in each region. Employing a qualitative multi-case study design, the research draws on direct observations and in-depth interviews with 32 informants, including local community members and tourism workers. Data were analyzed using thematic content analysis to identify patterns of language use, forms of tourism interaction, and community-led preservation efforts. The findings indicate a consistent pattern across all regions: local languages remain active in domestic and ritual contexts, shift into passive use among younger generations, and become endangered in high-intensity tourism zones such as Kuta–Seminyak, Malioboro, Lembang–Pangandaran, and Anyer–Tanjung Lesung. The shift is driven by tourism communication demands, youth linguistic preferences, industry service norms, and weakening intergenerational transmission. Despite these pressures, strong preservation strategies persist within customary communities, local educational initiatives, and cultural activities. The study highlights the need for a more integrated language preservation strategy involving government policy, the tourism sector, and local communities. The originality of this research lies in its cross-regional comparative analysis that explicitly links tourism activities to the vitality of local languages in Indonesia.